THE INFLUENCE OF INTEGRATED MARKETING COMMUNICATION STRATEGY IN THE FROZEN FOOD INDUSTRY IN SAMARINDA ANALYSIS OF REPURCHASE INTENTION, BRAND AWARENESS, CUSTOMER SATISFACTION AND CUSTOMER TRUST - Prapdopo; Andi Nurhasanah; Johan Lucas Away; Rima Melati (CV. RADJA PUBLIKA, 2025)
This study aims to analyze and prove the Influence of Integrated Marketing Strategy in the Frozen Food Industry in Samarinda Analysis of Repurchase Intention, Brand Awareness, Customer Satisfaction, and Customer Trust. This study used a questionnaire with a sample of 162 respondents in Samarinda City. This study uses a quantitative approach using path analysis processed with IBM SPSS Statistic 23 software and Structural Equation Modeling (SEM) with a sampling technique of accidental random sampling. The measurement scale used in this study uses a Likert scale with a score of 1 to 5. In this study, the researcher conducted an instrument test, namely a validity test and a reliability test as well as a classical assumption test such as a normality test and a multicollinearity test which were then carried out an estimation test and a structural model fit test. Based on the structural model used in this study